2003
DOI: 10.1002/jnr.10833
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen interacts with the IGF‐1 system to protect nigrostriatal dopamine and maintain motoric behavior after 6‐hydroxdopamine lesions

Abstract: The most prominent neurochemical hallmark of Parkinson's disease (PD) is the loss of nigrostriatal dopamine (DA). Animal models of PD have concentrated on depleting DA and therapies have focused on maintaining or restoring DA. Within this context estrogen protects against 6-hydroxdopamine (6-OHDA) and 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP) lesions of the nigrostriatal DA pathway. Present studies tested the hypothesis that neuroprotective estrogen actions involve activation of the insulin-like grow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
106
2
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 135 publications
(118 citation statements)
references
References 67 publications
9
106
2
1
Order By: Relevance
“…Pretreatment with oestrogen or IGF-I significantly prevents the loss of substantia nigra compacta neurons and the related motor disturbances. Blockage of IGF-I receptors by intracerebroventricular JB-1 attenuates the neuroprotective effects of both oestrogen and IGF-I (Quesada & Micevych 2004). These findings suggest that the neuroprotective actions of oestradiol and IGF-I after brain injury depend on the coactivation of both oestrogen receptors and IGF-I receptor.…”
Section: Interaction Of Oestradiol and Igf-i On Neuroprotectionmentioning
confidence: 75%
“…Pretreatment with oestrogen or IGF-I significantly prevents the loss of substantia nigra compacta neurons and the related motor disturbances. Blockage of IGF-I receptors by intracerebroventricular JB-1 attenuates the neuroprotective effects of both oestrogen and IGF-I (Quesada & Micevych 2004). These findings suggest that the neuroprotective actions of oestradiol and IGF-I after brain injury depend on the coactivation of both oestrogen receptors and IGF-I receptor.…”
Section: Interaction Of Oestradiol and Igf-i On Neuroprotectionmentioning
confidence: 75%
“…Nevertheless, supporting our findings, Dhandapani et al (2005) reported recently that transforming growth factor-␤ mediates the neuroprotective effect of estradiol and involves Akt phosphorylation in cultures of primary rat cortical astrocytes. In addition, estrogen was reported to interact with the IGF-I system to protect nigrostriatal dopamine and maintain motor behavior in 6-hydroxydopaminelesioned rats (Quesada and Micevych, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…This preliminary evidence suggests that estrogen protection in the striatum may involve ER-α, but additional studies such as examining estrogen ability to protect the striatum against MPTP-induced damage in ER-knockout mice would help add important corroborating evidence for the role of ER in estrogen action in the striatum. Furthermore, alternative pathways for estrogen neuroprotection must be considered as well, as work by Quesada and Micevych [141] has provided evidence that estrogen interacts with the IGF-1 system to protect nigrostriatal dopaminergic neurons and maintain motor function after 6-hydroxydopamine lesion animals. Finally, it should be added that estrogen has also been shown to reduce the dyskinetic effects produced by MPTP in monkeys, suggesting that estrogen's beneficial effects on the dopaminergic system applies to higher species [142].…”
Section: Parkinson's Diseasementioning
confidence: 99%